ChemInform Abstract: Asymmetric anti‐Selective Michael Reaction of Imidazole‐Modified Ketones with trans‐β‐Nitroalkenes. Issue 24 (June 2015) - Yang, Dongxu; Wang, Linqing; Li, Dan; Han, Fengxia; Zhao, Depeng; Wang, Rui
Abstract: The highly enantioselective reaction between imidazolyl ketones and nitroalkenes furnishes the anti‐selective adducts in high yields in the presence of a novel bromothiophene‐derived chiral diamine ligand.